Job Satisfaction of Tax Inspectors of the DGT Regional Office of Central Java I Predictors of Education and Professionalism - Sudarman, Sudarman; Kusuma, Septian Yudha (Global Health Science Group, 2022)
This study aims to analyze the education and professionalism of tax inspectors' job satisfaction at the DGT Regional Office of Central Java I. Research design uses qualitative descriptive research using primary data and skunder. The analysis of the study used multiple partial regression, regression equation and termination test. The sampling technique uses non probability sampling with the type of total sampling. Because the total population only amounts to 36 people, the population is taken entirely to be used as a sample. The results of the study explained that education and professionalism affect tax job satisfaction of the Central Java DGT Regional Office I. This proves that job satisfaction increases due to the role of education, work experience and professionalism of the examiner.